Teaching and Statistical Training - Ulrich Rendtel (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
The availability of well-educated researchers is necessary for the fruitful analysis of social and economic data. The increased data offer made possible by the creation of the Research Data Centers (RDCs) has resulted in an increased demand for PhD students at the master's or Diplom levels. Especially in economics, where we find intense competition among the various individual subjects within the course of study, survey statistics has not been very successful in laying claim to a substantial proportion of the coursework and training. The situation is more favorable in sociology faculties. This article argues that the creation of new CAMPUS Files would help foster statistical education by providing public use files covering a wider range of subjects. It also presents some suggestions for new CAMPUS Files along these lines. Additionally, it argues for the establishment of master's programs in survey statistics to increase the availability of well-trained statisticians. An outline of such a master's program is presented and current PhD programs are evaluated with respect to training in survey statistics. Training courses are also offered outside the university that promote the use of new data sets as well as expanding the knowledge of new statistical methods or methods that lie outside standard education. These training courses are organized by the RDCs, (i.e. the data producers), the Data Service Centers, or by GESIS (Leibniz Institute for the Social Sciences). The current tendency to strengthen ties and collaborate with universities should be supported by making it possible to earn academic credit for such courses.
Keywords: 330; master's programs; survey statistics; campus files; statistical training